Comprehensive Studies on Rarefied Jet and Jet Impingement Flows with Gas-Kinetic Methods (Communications in Computational Physics, 2017)
This paper presents comprehensive studies on two closely related problemsof high speed collisionless gaseous jet from a circular exit and impinging on an inclinedrectangular flat plate, where the plate surface can be diffuse or specular reflective.Gas-kinetic theories are adopted to study the problems, and several crucialgeometry-location and velocity-direction relations are used. The final complete resultsinclude flow-field properties such as density, velocity components, temperature andpressure, and impingement surface properties such as coefficients of pressure, shearstress and heat flux. Also included are the averaged coefficients for pressure, friction,heat flux, moment over the whole plate, and the averaged distance from the momentcenter to the plate center. The final results include complex but accurate integrationsinvolving the geometry and specific speed ratios, inclination angle, and the temperatureratio. Several numerical simulations with the direct simulation Monte Carlomethod validate these analytical results, and the results are essentially identical. Exponential,trigonometric, and error functions are embedded in the solutions. The resultsillustrate that the past simple cosine function approach is rather crude, and should beused cautiously. The gas-kinetic method and processes are heuristic and can be usedto investigate other external high Knudsen number impingement flow problems, includingthe flow-field and surface properties for high Knudsen number jet from an exitand flat plate of arbitrary shapes. The results are expected to find many engineeringapplications.